Prosthetic rehabilitation of a severely resorbed ridge using a maxillary complete denture opposing a mandibular implant-supported overdenture: a case report - Ahmad, Norfaezah; Wan Nik, Wan Noor Nazayan; Mohd. Nor, Hikmah; Chu, Seng Boon (IIUM Journal of Orofacial and Health Sciences, 2025)
A 64-year-old patient was referred to the prosthodontics clinic with a history of two failed mandibular dentures and significant functional impairment. The patient had been completely edentulous since the age of 40 due to advanced chronic periodontal disease. She experienced progressive loss of retention and stability of the mandibular prostheses, resulting in discomfort, pain, and difficulty with speech and mastication. The intraoral examination revealed severe alveolar bone resorption of both arches, shallow palatal vault, and reduced maxillary and mandibular arch height and width. The existing dentures, partially lined with soft lining material, exhibited poor retention and stability. The maxillary denture lacked posterior seal, and the mandibular denture, despite adequate extension, was considered intolerable. A treatment plan consisting of a combination of maxillary conventional complete denture and mandibular implant-supported overdenture was executed. This approach was found to be a clinically effective, cost-efficient, and predictable solution in addressing the patient’s concern for improved oral function.